Active substances of myxobacteria against plant diseases and their action mechanisms - Zhang, Lele; Bao, Liangliang; Li, Songyuan; Liu, Yang; Liu, Huirong (Frontiers in Microbiology, 2024)
Myxobacteria have a complex life cycle and unique social behavior. They can prey on plant pathogenic fungi, bacteria, and oomycetes in the soil by producing some enzymes and small molecule compounds. The enzymes mainly include β-1,6-glucanase, β-1,3-glucanase, chitinase, protease, peptidase, and formaldehyde dismutase. β-1,6-glucanase, β-1,3-glucanase, and chitinase can degrade the glycosidic bonds in the cell wall of plant pathogen, causing some holes to form on the cell walls of the plant pathogen. Proteases and peptidases can break plant pathogenic cells into many small fragments and facilitate extracellular digestion of proteins during myxobacterial predation. Formaldehyde dismutase converts formaldehyde to formate and methanol, it can help myxobactria protect themselves in the process of predation. Small molecule substances produced by myxobacteria include isooctanol, di-isobutyl phthalate, myxovirescin, cystobactamid derivatives, hyalodione, argyrin derivatives, Methyl (2R)-2-azido-3-hydroxyl-2-methylpropanoate and N-(3-Amino-2-hydroxypropyl)-N-meth-ylsulfuric diamide, etc. Isooctanol destroyed the cell wall and cell membrane of plant pathogen, causing intracellular reactive oxygen species (ROS) to accumulate, leading to apoptosis and cell death. Di-isobutyl phthalate had biofilm inhibitory activity against bacteria. Myxovirescin could inhibit the incorporation of diamibopimelic acid and uridine diphosphate-Nacetylglucosamine intobacterial cell wall and interfered with the polymerizaton of the lipid-disacchar-pentapeptide. Cystobactamid derivatives exerted their natural antibacterial properties by inhibition of bacterial gyrases. Hyalodione had broad antibacterial and antifungal activity. Argyrin derivatives inhibited protein synthesis by interfering with the binding of elongation factor G (EF-G) to ribosomes. Methyl (2R)-2-azido-3-hydroxyl-2-methylpropanoate and N-(3-Amino-2-hydroxypropyl)-N-meth-ylsulfuric diamide reduced the content of soluble proteins and the activity of protective enzymes (PPO, POD, PAL, and SOD) in plant pathogen, increased oxidative damage and cell membrane permeability. Myxobacteria, as a new natural compound resource bank, can control plant pathogenic fungi, oomycetes and bacteria by producing some enzymes and small molecule compounds, so it has great potential in plant disease control.